The Dichotomy Free and Literal Translation - Barbe, Katharina (Meta, 1996)
AbstractHistorically, the status of translation and translators has changed with the ascendance of monolingualism. Even today, translation is not fully recognized as an independent field of study, and translators as well as translation theorists are not without blame for this. The requirements for a good translation vary with each text. The concepts of free and literal translation are questionable and need to be rexamined. A cross-cultural study of translation including non-Indo-European languages may help us to break out of this dichotomy, as may the study of oral cultures.